(untitled) (Oxford ; Ames, Iowa, 2006)
Highly profitable and an important range of products within the dairy industry worldwide, the economic importance of fermented milks continues to grow. Technological developments have led to a wider range of products and increased popularity with consumers. In the second book to feature in the SDT series Fermented Milks reviews the properties and manufacturing methods associated with products such as yoghurt, buttermilk, kefir, koumiss milk-based fermented beverages and many other examples from around the globe, offering the reader: - A practically-oriented and user-friendly guide - Key commercially important information - Coverage of all the major stages of manufacture - Background to each product
Keywords: Fermented milk,Sữa lên men